SOME ASPECTS OF THE WATER CRISIS IN BULGARIA (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The failure of providing reliable water supply with standard water quality to the households is seen as a specific aspect of the water crisis. In this study, the drinking water supply of the households in Northeastern region of Bulgaria (Varna, Shumen, Dobrich, and Targovishte districts) for the period 2010-2021 was studied and analysed. During the studied period, the relative share of population affected by lack of drinking water supply for over 180 days per year varies between 0.0% in 2011 to 0.7% in 2020 of the total percentage of affected population on national scale. For Varna and Dobrich districts, the share of the affected population from prolonged interruptions in the water supply does not exceed 1%. The most severely affected is the Targovishte district’s population, where between 8.8% in 2010 and 24.3% in 2020 experience water supply regime with long, regular interruptions of water supply. In the municipality of Omurtag, approximately 80% of the population does not receive continuous water supply. Households in some of the villages in this municipality receive regulated water supply once every 480 hours. Based on the analysis, settlements with a regime of water supply and poor drinking water quality were identified, as well as the time intervals of supply interruption for the period studied. The main reasons for the manifestations of this specific aspect of the water crisis in Northeastern region of Bulgaria were identified. The shortage of water and the inability to provide households with the necessary water quantities with the required quality confronts Bulgaria with an ever-growing problem, the solution of which requires a complex institutional response, including from the water supply and sewerage sector.